1996
DOI: 10.1099/13500872-142-8-1989
|View full text |Cite
|
Sign up to set email alerts
|

The assimilation of sulfur from multiple sources and its correlation with expression of the sulfate-starvation-induced stimulon in Pseudomonas putida S-313

Abstract: Conditions were optimized for the batch growth of Pseudomonas putida 5-313 under sulfur-limited conditions. P. putida grew exponentially with sulfate as the sole source of sulfur, and growth was concomitant with the utilization of sulfate until it was exhausted. A further 20% of protein was synthesized after the apparent disappearance of sulfate. A mass balance for the utilized sulfate in cell material was calculated, given the observed molar growth yield of about 3.6 kg protein (mol S)-' and a sulfur content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 13 publications
(13 reference statements)
5
31
0
Order By: Relevance
“…1E; µ = 0.21 h -1 ) displayed a different pattern, with substrate exhaustion occurring well before the end of growth [cf. Beil et al (1996)]. The overall growth yield with sulfide was approximately 3 kg protein/mol S; with X-sulfate it was approximately 4 kg protein/mol S. Growth in all cases was monophasic, similar to the curves in Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…1E; µ = 0.21 h -1 ) displayed a different pattern, with substrate exhaustion occurring well before the end of growth [cf. Beil et al (1996)]. The overall growth yield with sulfide was approximately 3 kg protein/mol S; with X-sulfate it was approximately 4 kg protein/mol S. Growth in all cases was monophasic, similar to the curves in Fig.…”
Section: Resultssupporting
confidence: 63%
“…Kertesz et al (1993), Beil et al (1995), Beil et al (1996)]. We thus examined whether our Clostridium spp.…”
Section: Resultsmentioning
confidence: 99%
“…cysteine or thiocyanate, and derepressed during growth with other sulfur sources [ 16,18,20]. Regulation of aliphatic sulfonate desulfonation was studied in vivo in P. aeruginosa by measuring desulfonation of 4-phenylbutanesulfonate (100 PM) during growth of the cells in the presence of an excess (500 FM) of a second sulfur source (Fig.…”
Section: Regulation Ofdesulfonation Actmy By the Sulfur Supply To Thementioning
confidence: 99%
“…aromatic sulfonates and aromatic sulfate esters (Beil et al, 1995(Beil et al, , 1996. It has been shown that in E. coli, Pseudomonas putida and Pseudomonas aeruginosa, the phenomenon is due to repression by sulfate of the enzymes involved in the liberation of sulfur from organosulfur compounds (Beil et al, 1995 ;Kertesz, 1996;van der Ploeg et al, 1996).…”
Section: Introductionmentioning
confidence: 99%